Investigation on microstructure and high-temperature wear properties of high-speed laser cladding Inconel 625 alloy - Xiaoming Wang; Xuechong Ren; Yanpeng Xue; Benli Luan (Journal of Materials Research and Technology, 2024)
Inconel 625 alloy cladding layer was prepared by high-speed laser cladding (HLC) on Q245R steel substrate to improve the service performance of the structural components in the power industry in this work. A comprehensive study on the HLC Inconel 625 coating with different scanning speeds was conducted utilizing Scanning Electron Microscope (SEM), Transmission Electron Microscope (TEM), Laser Scanning Confocal Microscope (LSCM), X-Ray Diffraction (XRD), a microhardness tester, and an SRV-4 high-temperature friction and wear testing machine. The results show that the cladding layer's thickness and surface roughness decrease with the scanning speed increase. The cladding layers with different scanning speeds contain different microstructures. The phases mainly consist of γ-Ni and NbC. The microhardness of HLC coatings is generally higher than that of substrate, but decreased as the scanning speed increased. After the friction wear test at 500 °C, the cladding layer at the scanning speed of 2 m/min showed the best high-temperature wear resistance. The grain boundary area increases due to the formation of small-sized equiaxed dendrites, which resists dislocation slip and crack propagation, thereby enhancing high-temperature wear resistance. For the cladding layers at the higher scanning speed, the abrasive wear and the fatigue wear occur due to the precipitation of solid soluble elements such as Nb and Mo and the columnar crystal structures prone to deformation.